Perencanaan bisnis pempek tekwan Palembang Dapur Cindo - Hasmoro, Dhomas Agastya (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Pempek Tekwan Palembang Dapur Cindo is a business that focuses on selling snacks. This research aims to create a business plan by first knowing the positioning. This research uses quantitative methods. Researchers focus on selling products online through the top three service applications that are often used by the public, especially in DKI Jakarta, namely Gofood, Grabfood, and Shopeefood. Researchers sell pempek in two variations, namely ready-to-eat pempek and frozen pempek. The demographic bonus of the DKI Jakarta population is its productive age, and the habit of using online shopping applications is what encourages sellers to do active buying and selling through these applications. Satisfaction value and positioning are then processed using design thinking for business planning, which contains strategy, targeting, and positioning, which contain marketing, product, operational, and risk strategies. Business feasibility is also calculated in the study to find out whether the product is feasible to be sold. The NPV value is IDR 345,783,308 with a payback period of 1 year and 9 months and an IRR of 81%.